2021
DOI: 10.1177/0734371x21994185
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mediating Effect of Internal Communication on Strategic Human Resource Management and Perceived Performance: An Intersectoral Comparison

Abstract: Using five waves of Korean Workplace Panel Survey (KWPS) data, we examine the mediating effects of internal communication channels on the relationship between strategic human resource management and organizational performance. Comparing public, nonprofit, and for-profit organizations, we demonstrate significant sector differences in communication. Our analyses show that only for-profit firms have been able to tap into the advantages of internal communication channels in an effort to improve the alignment betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…From the point of view of strategic management and human resource theories, internal communication is highly relevant for companies. They provided that they cultivate an organisational climate open to innovation, intrapreneurship, creativity and corporate happiness (Andersson, 2019;Cuesta-Valiño et al, 2022;Lee and Kim, 2021;Suh and Battaglio, 2021;Venn and Berg, 2013). Based on this evidence, and other multiple aspects, a large number of companies are gradually implementing actions aimed at enhancing internal communication among their employees through the implementation of onboarding, team building or happiness management (Ravina-Ripoll et al, 2021a, b;Ver ci c and Spoljari c, 2020).…”
Section: Internal Communication As a Predictor Of Happiness At Workmentioning
confidence: 99%
“…From the point of view of strategic management and human resource theories, internal communication is highly relevant for companies. They provided that they cultivate an organisational climate open to innovation, intrapreneurship, creativity and corporate happiness (Andersson, 2019;Cuesta-Valiño et al, 2022;Lee and Kim, 2021;Suh and Battaglio, 2021;Venn and Berg, 2013). Based on this evidence, and other multiple aspects, a large number of companies are gradually implementing actions aimed at enhancing internal communication among their employees through the implementation of onboarding, team building or happiness management (Ravina-Ripoll et al, 2021a, b;Ver ci c and Spoljari c, 2020).…”
Section: Internal Communication As a Predictor Of Happiness At Workmentioning
confidence: 99%
“…Albeit the presence of effective factors contributing to the successful implementation of green human resource management in organizations, there are possibilities that various hurdles would impede GHRM from implementation. According to several researchers (e.g., Alwan & Nori, 2021;Cuellar-Molina et al, 2018;Mtembu, 2017;Suh & Battaglio, 2021), the barriers of GHRM have different natures such as internal to the organizations or emanated from the external environment and directly or indirectly affect green human resource management implementation in organizations. However, specific to this study, the researchers have used apparent factor categories suggested by Bombiak (2020) these are: Management Factors, Technological Factors, Cultural Factors, Staff Factors, and those factors categorized under "Others"to investigate barriers to implementing green human resource management in organizations, via review of extant GHRM studies.…”
Section: Barriers To Green Human Resource Management (Ghrm) Implement...mentioning
confidence: 99%
“…Leading scholars and analysts typically concentrate on three distinct approaches to the theoretical interpretation of the relationship between HRM and organizational performance. These consist of (a) Approach to universalism or best practices, (b) Fit or contingency and (c) Resource-based view (Schotter et al, 2021;Suh & Battaglio, 2021;Sabir et al, 2015). The best practice and contingency approach emphasize how the human resource can be a competitive asset for businesses.…”
Section: Strategic Human Resource Management Rule-breaking and Job Sa...mentioning
confidence: 99%